2020
DOI: 10.1038/s41598-020-71299-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability and genotype affect major nutritional quality parameters of tef grain grown under irrigation

Abstract: Worldwide demand for tef (Eragrostis tef) as a functional food for human consumption is increasing, thanks to its nutritional benefits and gluten-free properties. As a result, tef in now grown outside its native environment in Ethiopia and thus information is required regarding plant nutrition demands in these areas, as well as resulting grain health-related composition. In the current work, two tef genotypes were grown in Israel under irrigation in two platforms, plots in the field and pots in a greenhouse, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Few studies have analyzed the effect of N fertilization on polyphenols in grains, with their results being divergent. Engert et al [2] and Ma et al [28] found that total phenolics increased in wheat grains due to N fertilization, while N availability affected negatively total phenolics in tef grains [64] and sesame seeds [65]. Stumpf et al [66] found, on the contrary, that total phenolic concentration was not affected by N treatment in wheat grains.…”
Section: A High Nitrogen Supply Increases Total Grain Polyphenols Dumentioning
confidence: 99%
“…Few studies have analyzed the effect of N fertilization on polyphenols in grains, with their results being divergent. Engert et al [2] and Ma et al [28] found that total phenolics increased in wheat grains due to N fertilization, while N availability affected negatively total phenolics in tef grains [64] and sesame seeds [65]. Stumpf et al [66] found, on the contrary, that total phenolic concentration was not affected by N treatment in wheat grains.…”
Section: A High Nitrogen Supply Increases Total Grain Polyphenols Dumentioning
confidence: 99%
“…51 Available studies support the idea that diabetic patients can get enough amount of essential fatty acids from teff and it is a promising food type used to manage acute and chronic diabetic complications. 2,20,52,53…”
Section: Essential Fatty Acid Composition Of Teff and Diabetesmentioning
confidence: 99%
“…Teff is a warm-season annual cereal and the only cultivated species in the genus Eragrostis which has originated in Ethiopia [14][15][16][17]. It is a whole grain and superior than other cereals due to being naturally gluten free and is the dominant source of nutrients like carbohydrates, amino acids, minerals, dietary fibers, proteins, dietary polyphenols, starch, and vitamins [5,16,18,19], volatiles like aldehydes, ketones and alcohols [16], and is rich in unsaturated fatty acids like linoleic, oleic and linolenic acids [17,20]. The ratio of ω-6/ω-3 found in the white and brown teff flour was almost consistent with the suggested 1-2:1 ratio and is recommendable for the normal human growth and development.…”
Section: Introductionmentioning
confidence: 99%